Case reportBNP in the differential diagnosis of amiodarone-induced pulmonary toxicity: a case report and review of the literature - Grabowski, Marcin; Małek, Łukasz A.; Karpiński, Grzegorz; Filipiak, Krzysztof J.; Opolski, Grzegorz (Archives of Medical Science, 2006)
A 70-year old man with a history of surgically treated lung cancer, ST-elevation myocardial infarction treated with primary angioplasty, congestive heart failure, and on treatment with amiodarone was admitted to the intensive care unit due to exacerbation of dyspnea. We propose a differential diagnosis of acute congestive heart failure and amiodarone-induced pulmonary toxicity with the use of B-type natriuretic peptide (BNP) plasma concentration analysis. The case report is followed by a literature review.